Implementasi Strategic Thinking Dan Visioning Kepemimpinan Kepala Sekolah - Nazib, Fiqra; Hidayat, Rais; Ainissyifa, Hilda (Jurnal Manajemen Pendidikan Dasar, Menengah dan Tinggi [JMP-DMT], 2024)
The aims of this research are (1) to determine the concept of Strategic Thinking and Visioning leadership of the Principal at Asshiddiqiyah Garut Junior High School (SMP); (2) to determine the implementation of Strategic Thinking and Visioning leadership of the Principal at Asshiddiqiyah Garut Junior High School (SMP); (3) to determine the supporting and inhibiting factors for strategic thinking and visioning leadership of the principal at Asshiddiqiyah Garut Junior High School (SMP). This research method uses descriptive qualitative methods to describe, describe, explain, explain and answer questions. The subjects of this research were principals and teachers at Asshiddiqiyah Garut Junior High School (SMP). The results of this research are that strategic thinking and visioning leadership of school principals can analyze the challenges and opportunities faced by educational institutions, as well as identify concrete steps that need to be taken to achieve the vision and describe the ideal future picture of educational institutions at Asshiddiqiyah Middle School in Garut.